BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEKERJA DALAM PENERAPAN SAFE BEHAVIOR DI PT. HANIL JAYA STEEL - Nindya Septiani (Universitas Airlangga, 2017)
ABSTRACTOccupational Safety and Health (OSH) behaviour is influenced by predisposing, enabling, and reinforcing factors. Occupational accidents caused by various factors at work can be avoided, if the worker and the company management have a good will to prevent it. OSH behaviour is necessary for the prevention of occupational accidents. The purpose of this research was to describe the association between predisposing, enabling and reinforcing factors with behaviour of workers (mill line rolling mill 3) on the implementation of safe behaviour in PT. Hanil Jaya Steel. This was an observational descriptive study with cross sectional approach and carried out among 26 respondents. The variables studied were age, length of employment, level of knowledge, attitude, frequency of worker’s OSH training, frequency of OSH training which provide by the company, availability of personal protector equipment, regulation assembly, standard operational procedures assembly, co-workers’ support, supervisor’s support, reward, punishmnet and safe behaviour. The strength of relationship between variables were analyzed by using Contingency Coefficient (C). The results showed that there were weak association between level of knowledge, frequency of worker’s OSH training and behaviour (C = 0.085 and C = 0.255, respectively). There were moderate association between age, length of employment, co-workers’ support and behaviour (C = 0.398, C = 0.328 and C = 0.400, respectively). And Also there was strong association between attitude and behaviour (C=0.556). It is recommended that the company providing OSH training section frequently for all workers, improving the monitoring system of workers, and providing reward and punishment program, in order to improve their safe behaviour in preventing occupational accident in workplace. Keywords: predisposing, enabling, reinforcing, safe behaviour ABSTRAKPerilaku K3 dipengaruhi oleh faktor predisposisi, faktor pemungkin, dan faktor penguat. Kecelakaan kerja yang disebabkan oleh berbagai faktor dalam pekerjaan bisa dihindarkan, apabila pekerja dan pimpinan perusahaan ada kemauan baik untuk mencegahnya. Perilaku K3 diperlukan untuk pencegahan kecelakaan kerja. Tujuan penelitian ini adalah untuk mendeskripsikan hubungan antara faktor predisposisi, faktor pemungkin, dan faktor penguat mengenai perilaku pekerja (unit mill line rolling mill 3) terhadap penerapan perilaku aman di PT. Hanil Jaya Steel. Penelitian ini merupakan penelitian observasional deskriptif dengan pendekatan cross sectional dan dilakukan pada 26 responden. Variabel yang diteliti adalah umur, masa kerja, tingkat pengetahuan, sikap, frekuensi pelatihan K3, frekuensi penyelenggaraan pelatihan K3, ketersediaan APD, penempelan/pemasangan peraturan, penempelan/pemasangan SOP, dukungan teman kerja, dukungan pimpinan/pengawas, reward, punishment dan perilaku aman. Kuat hubungan antar variabel dianalisis dengan menggunakan uji Koefisien Kontingensi (C). Hasil penelitian menunjukkan terdapat hubungan yang lemah antara pengetahuan dan frekuensi pelatihan K3 dengan perilaku aman (C = 0.085 dan C = 0.255, berturut-turut). Terdapat hubungan yang sedang antara umur, masa kerja, dukungan teman kerja dengan perilaku aman (C = 0.398, C = 0.328 dan C = 0.400, berturut-turut) serta terdapat hubungan yang kuat antara sikap dengan perilaku aman (C=0.556). Disarankan bagi pihak perusahaan untuk mengadakan pelatihan K3 secara berkelanjutan kepada semua pekerja, meningkatkan sistem pengawasan pekerja, serta mengadakan program reward dan punishment dalam rangka meningkatkan penerapan perilaku aman pekerja dalam pencegahan kecelakaan kerja di tempat kerja. Kata kunci: predisposisi, pemungkin, penguat, perilaku aman